COOPERATION OF UNIVERSITY EDUCATIONAL PROCESS SUBJECTS BASED ON COMPETENCE-ORIENTED APPROACH IN UPBRINGING - Tatyana A. Lopatukhina; Anna V. Osipova (Advanced Engineering Research)
The authors competence - oriented approach concept in higher education is based on the choice of the moral and spiritual priorities. The identification of the upbringing competences, which university educational process sub jects should possess, is considered from this perspective. The authors treatment of the basic concepts, te rms, and defin itions is given. Two priority - oriented matrices on whose basis the real development level of the competences in u pbringing is measured a re given.